PENINGKATAN TARAF KESEHATAN GIGI DAN MULUT KOMUNITAS SEKOLAH DASAR DAN MASYARAKAT KELURAHAN JATIPULO KECAMATAN PALMERAH, JAKARTA BARAT - Ciptadhi Tri Oka B; Adrian Nova Fitri; Ricky Anggara Putranto (Jurnal AKAL : Abdimas dan Kearifan Lokal, 2020)
According to Riskesdas 2018 data, the prevalence of caries in Indonesia is 88.8%. Maintaining healthy teeth and mouth is very important because oral health is an integral part of body health which is interrelated with general health in our bodies. The community in the elementary school environment and the people of Petamburan Village, Jatipulo, West Jakarta, have a low economic level, where people prioritize meeting their daily basic needs compared to spending on maintenance and treatment of teeth and mouth. Through counseling and dental and oral health services, it will improve understanding and quality of dental and oral health in the school community and community in the jatipolo-West Jakarta district. About 90 primary school communities and 50 communities participated in this program. There were 86 people from 90 elementary school communities and 48 people from 50 people who received treatment in the form of filling and extractions. From the data obtained, around 99.95% of the total primary school community and the community have dental and oral health problems. Therefore it is necessary to provide ongoing assistance to improve the level of oral health in the Jatipulo area, West Jakarta